Freight transport, food production and consumption in the United States of America and in Europe: Or how far can you ship a bunch of onions in the United States? - Stefanie Böge (Wuppertal Institut für Klima, Umwelt, Energie, 1996)
CO2-emissions from traffic - increasingly from freight transport - are growing, es-pecially in the highly developed industrialized countries. The answers to thisenvironmentally problematical development are technical ones mainly: Admi-nistrators and scientists try to improve engines, transportation modes and logisticstrategies. Freight transport is influenced by production, consumption, land-usepatterns and life-styles. But these fundamental determinants of increasing trafficare rarely given the same priority as the technical solutions.The main focus of this paper is on freight transportation and food supply in theUnited States and in Europe especially in Germany. Organic, resp. healthy andsafe food is a growing demand in both countries. People who consume organicfood often believe that this contributes to an environmentally sound behaviour.But transportation issues are not or rarely taken into consideration so far, although long distance transport not only needs energy, it as well influences quality, freshness and taste of food.On both sides of the Atlantic, in freight transportation and food supply can befound a lot of differences as well as similarities. Main differences to the U.S. fromthe European standpoint are e.g. the bigger land area and larger and much moreconcentrated economic units. Quite naturally one can find a higher volume oflong distance freight transport than in Europe. Similarities can be observed, butvery often they present themselves in another extent, e.g. the trend towards pri-vatisation and liberalisation, to more extended suburbanisation or to an unreflec-ted way of consumer behaviour. In addition, this report raises some new questi-ons: is the 'technological solution' of environmental problems the only way.What can be done to include lifestyles and consumer behaviour into a new strategy.
urn:nbn:de:bsz:wup4-opus-3799
Keywords: 330